MULTI-CENTRE STUDIES OF THE GLOBAL IMPACT OF ENDOMETRIOSIS AND THE PREDICTIVE VALUE OF ASSOCIATED SYMPTOMS. - Nnoaham, K; Sivananthan, S; Hummelshoj, L; Jenkinson, C; Webster, P; Kennedy, S; Zondervan, K (2009)
Endometriosis can be difficult to diagnose clinically and models that use symptoms to predict whether the disease is present or not are based on limited patient populations. Endometriosis also influences health-related quality of life, but little is known about its impact across the world. We therefore initiated two integrated multicentre studies to collect prospective, standardised, epidemiological data, to 1) examine the global impact of endometriosis and relative effect of risk-factors, and 2) develop a symptom-based diagnostic tool.The Global Study of Women's Health (GSWH) and the Women's Health Symptom Survey (WHSS) prospectively recruit 18-45 year old women having a laparoscopy across 23 and 19 centres, respectively, worldwide. Women with a previous surgical diagnosis of endometriosis are excluded. Multi-lingual patient questionnaires and a surgical questionnaire, incorporating validated instruments, are used to collect the data. The GSWH aims to recruit >2,000 women by December 2009; the WHSS to recruit 1,000 women in each of the two model-generating and validation stages.A six-week pilot study in Oxford, UK, established the feasibility of the study protocols. Of 32 eligible women, 27 participated (response rate - 84.4%); 26% completed the questionnaire online. Endometriosis was found in 47.4%. Extrapolating the recruitment rates from the pilot study, the target sample sizes for the GWSH and WHSS were deemed feasible.Using standardised data collection, the GSWH and WHSS will provide insight into the global impact of endometriosis and develop a validated, symptom-based, diagnostic tool. They have the potential to provide the basis for future, longitudinal, follow-up studies and a collaborative Endometriosis Biobank implementing standardised collection of DNA and tissue samples.